2019
DOI: 10.1161/strokeaha.118.023443
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Stroke in Patients With Sepsis and Bloodstream Infections

Abstract: Background and Purpose— Sepsis has been identified as a trigger for stroke, but the underlying mechanisms and risk factors that predispose patients with sepsis to increased stroke risk remain unclear. We sought to identify predictors of stroke after sepsis and bloodstream infections. Methods— The 2007–2009 California State Inpatient Database from the Health Care Utilization Project was used to identify patients over the age of 18 years an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 29 publications
2
32
1
1
Order By: Relevance
“…The novelty of this study is a first to report that 97.2% of sepsis patients had a SABD with bad outcome, and unused a rapid antibiotic treatment within the initial 0.5 to 3.0 hours after an early suspected infection event plays a vital role in advancement of high morbidity and high risk of death in SABD. In addition, this high prevalence of SABD with bad outcome can also be explained by the following several points: (1) the low prevalence of SAE in the ICU was from a population without stroke or traumatic brain injure [11,12], whereas, our current study is included these septic patients from stroke and trauma [2,13,15]; (2) our SABD patients were generally associated with a SIRS ≥2, which involves the pathogenesis of SABD contributed by Bone [27], i.e., the cytokines lead to blood brain barrier leakage and cell death [28]. A mixed SABD can be considered if accompanied by a primary brain injure; (3) most SABD in our series is presented with MODS, and the previous studies also indicated that sepsis patients with MODS were more likely to exhibit a SAE [12,21,29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The novelty of this study is a first to report that 97.2% of sepsis patients had a SABD with bad outcome, and unused a rapid antibiotic treatment within the initial 0.5 to 3.0 hours after an early suspected infection event plays a vital role in advancement of high morbidity and high risk of death in SABD. In addition, this high prevalence of SABD with bad outcome can also be explained by the following several points: (1) the low prevalence of SAE in the ICU was from a population without stroke or traumatic brain injure [11,12], whereas, our current study is included these septic patients from stroke and trauma [2,13,15]; (2) our SABD patients were generally associated with a SIRS ≥2, which involves the pathogenesis of SABD contributed by Bone [27], i.e., the cytokines lead to blood brain barrier leakage and cell death [28]. A mixed SABD can be considered if accompanied by a primary brain injure; (3) most SABD in our series is presented with MODS, and the previous studies also indicated that sepsis patients with MODS were more likely to exhibit a SAE [12,21,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, some epidemic studies of SAE showed that a low prevalence varies from 17.7% to 53% of patients with sepsis in ICU, which is unfortunately ruled out stroke or traumatic patients [11,12]. Indeed, acute stroke and traumatic brain injury is more likely to have a secondary sepsis [2,[13][14][15]. However, whether the prevalence of sepsis in ICU patients with critically ill, including acute stroke and traumatic brain injury, would present a leading high prevalence of SABD, which is still unknown.…”
mentioning
confidence: 99%
“…The role of sepsis as a risk factor for stroke, myocardial infarction, and new-onset atrial fibrillation has been described, and illustrated that patients with concomitant coagulopathy, congestive heart failure, renal failure and other circulation disorders had increased the risk of stroke after sepsis with the risk remaining up to a year after the sepsis event. 37 More common infections, such as respiratory tract infections or influenza-like illness (ILI), have been identified as both a potential chronic risk factor and an acute trigger for stroke and myocardial infarction. Moreover, risk of infections and stroke/MI share several similarities.…”
Section: Accepted Articlementioning
confidence: 99%
“…Patients with infection are often accompanied with changes of biochemical indexes, such as albumin (ALB), glucose (GLU), alanine transaminase (ALT), and aspartate transaminase (AST). Some clinical parameters, including white blood cell (WBC), platelets (PLT), C reaction protein (CRP), procalcitonin (PCT), interleukin-6 (IL-6) and d-dimer (D-D) are commonly used in diagnosing infection [5][6][7][8][9]. However, these parameters have not been widely studied in hematological malignancy patients.…”
Section: Introductionmentioning
confidence: 99%